The use of behavioural additionality in innovation policy-making - Abdullah Gök; Jakob Edler (The University of Manchester, Manchester Business School, 2011)
The overarching aim of this paper is to contribute to a better understanding of how the main target variable of innovation policy - change in behaviour - can be better conceptualised and put into practice in evaluation and policy making. The paper first develops a theoretical framework of the concept of behavioural additionality. On that basis it looks in detail at the way behavioural additionality is operationalised in evaluation practice and how the concept is discussed and applied in the interaction between policy-makers and evaluators. The paper utilises a statistical analysis of 171 innovation policy evaluations, a text analysis of selected behavioural additionality evaluation reports and finally a number of in-depth case studies of evaluations. Based on the theoretical considerations and the empirical findings, the paper identifies three different uses of behavioural additionality in innovation policy evaluations. It concludes that despite the widespread use of the behavioural additionality concept, an improved theoretical basis and serious methodological improvements are needed to realise the full potential of this concept for evaluation and policy practice
Keywords: 330; Innovationspolitik; Wirkungsanalyse; Bewertung; Verhaltensökonomik